Análisis del tratamiento de noticias relacionadas al femicidio publicadas en los diarios Correo, Nacional y Opinión durante el año 2015. - Sánchez Montoya, Oscar (2016)
The present research work is part of the titration work to be able to incorporate as Licdo. In social communication at the Technical University of Machala, it is based on the analysis of the journalistic treatment of the case of femicide in the year 2015. The methodology used in this research is the qualitative method, mainly based on the contents through the application Of the analysis, that is to say, with the interrelation of the people in the interviews will analyze the pertinent, practical treatment, by the journalists of the print media Correo, El Nacional and Opinión, with the support of official sources by The Office of the Prosecutor, the National Police, relatives, witnesses and the journalist's own investigation into the cases of femicide arising in the Province of El Oro. The first chapter covers the treatment of information that varies and involves, on the one hand, interviewees from the media Communication of the written press, prosecutor's office, feminist groups and relatives of victims who contributed with their statements, because there was a timely approach with each of them. The second chapter describes the different knowledge to be developed in the research units, the results are analyzed under the photographic aspects, titles of the back covers of the year 2015, will generally be evidenced the handling of the news of red chronicle in the newspapers Correo, El Nacional And opinion, showing the useful relationship that exists in the decision-making, the immediacy, the internal and external competitiveness of the news in the newspaper, exposes the way they work today with the treatment news, not leaving and less avoiding the sensationalism.